Efficiency of δ-Tocopherol in Inhibiting Lipid Oxidation in Emulsions: Effects of Surfactant Charge and of Surfactant Concentration - Tamara Martínez-Senra; Sonia Losada-Barreiro; Carlos Bravo-Díaz (MDPI AG, 2023)
Charged interfaces may play an important role in the fate of chemical reactions. Alterations in, for instance, the interfacial acidity of emulsions induced by the charge of the surfactant head group and associated counterions may change the ionization status of antioxidants, modifying their effective concentrations. The chemical reactivity between interfacial reactants and charged species of opposite charge (protons, metallic ions, etc.) is usually interpreted in terms of pseudophase ion-exchange models, treating the distribution of charged species in terms of partitioning and ion exchange. Here, we focus on analyzing the effects of charged interfaces on the oxidative stability of soybean oil-in-water (o/w) emulsions prepared with anionic (sodium dodecyl sulfate, SDS), cationic (cetyltrimethylammonium bromide, CTAB) and neutral (Tween 20) surfactants, and some of their mixtures, in the presence and absence of δ-tocopherol (δ-TOC). We have also determined the effective concentrations of δ-TOC in the oil, interfacial and aqueous regions of the intact emulsions. In the absence of δ-TOC, the relative oxidative stability order was CTAB < TW20 ~ TW20/CTAB < SDS. Surprisingly, upon the addition of δ-TOC, the relative order was SDS ≈ TW20 << TW20/CTAB < CTAB. These apparently surprising results can be rationalized in terms of the nice correlation that exists between the relative oxidative stability and the effective interfacial concentrations of δ-TOC in the various emulsions. The results emphasize the importance of considering the effective interfacial concentrations of antioxidants in interpreting their relative efficiency in emulsions.